Penerapan Metode Wetonan dalam Membaca Kitab Kuning Santri di Pondok Pesantren Al-Islam Kemuja - Sentia, Meliza; Anwar, Muhammad Rofiq (LENTERNAL: Learning and Teaching Journal, 2023)
The researchers took this problem because there were some obstacles in the implementation of the learning of the yellow book in the Pondok Pesantren Al-Islam Kharja, namely: first, the ability of the centri in understanding yellow books is still low because they have not understood the Arabic language. Second, the low-centered mastery of the study of the Yellow Book Third, the difficulty of reading and understanding the contents of yellow text So, we need a proper method of dealing with the problem. This research has several purposes, namely: First, to find out how to apply the method of wetonan in reading the yellow book of the centurion in the Pondok Pesantren Al-Islam Kulaja. The method used in this research is qualitative. In the collection of data, observation techniques, interviews, and documentation are used. As for processing techniques and data analysis, they are done with data reduction, presentation of data, and drawing conclusions. The results of this study show that in the application of the method of wetonan in the reading of the yellow book of the clergy in the Pondok Pesantren Al-Islam, worship has three important components in the stages of learning the yellow book, namely planning, implementation, and evaluation. The application of the wetonan method in reading the yellow book of the centurion in the Pondok Pesantren Al-Islam Kloja can increase the interest of centurions in the learning of yellow books, as seen from the aspects of centurians who are active in following learning in the classroom. so that the understanding of the material that has been studied does not just disappear and can also develop a high interest in learning.